FREQUENCY OF NECK PAIN AND ITS IMPACT ON ACTIVITIES OF DAILY LIFE IN MADRASSA STUDENTS AT HAYATABAD PESHAWAR - Qamar, Kashif; Khan, Seema; Rehman, Saira; Darain, Haider; Rehman, Mujeeb Ur (Annals of Allied Health Sciences, 2019)
OBJECTIVE: To determine frequency of neck pain and its impact on activities of daily life in madrassa students at Hayatabad Peshawar, Khyber Pakhtunkhwa. METHODS: A cross sectional study was conducted at five different full-time madrassas at Hayatabad Peshawar. Neck Disability Index (NDI) questionnaire was used to collect data through convenience sampling from 302 students of madrassas who were willing to participate. All the participants were male and were divided into two groups Ilam and Hifz group. SPSS version 20 was used for data analysis. RESULTS: Out of 302 male students, 101 (33.4%) were suffering from neck pain. The total disability on the basis of groups was found to be 60.6% in ilam group and 39.4% in hifz group with a p value of 0.434 which shows is statistically insignificant. On the basis of madrassas, the statistical significant differences were found i.e. (p=0.001), and severe disability was only reported in madrassa darul uloom which was 1.8%. There is negative correlation of neck pain with age and BMI and a positive correlation with study duration but the results were statistically insignificant. All activities of daily living were affected by neck pain causing headache 234 (77.5%) in majority, followed by concentration 137 (45.3%) and then reading 130 (43.1%). CONCLUSION: It is concluded that students of madrassa are prone to develop neck pain and almost 1/3rd of the population were having neck pain. No statistical significant differences were found between Ilam and Hifz group regarding neck disability, but statistical differences were found among madrassas. There is negative correlation of neck pain with age and BMI and a positive correlation with study duration but the results were statistically insignificant. Neck pain can also have an impact on activities of daily life.